Prevalence of Ectoparasites in Tilapia (Oreochromis niloticus) in Sidoarjo, Indonesia - Sari, Aulia Puspita; Koesdarto, Setiawan; Lestari, Tita Damayanti; Hastutiek, Poedji; Yunus, Muchammad; Herupradoto, Eduardus Bimo Aksono; Khairullah, Aswin Rafif; Ayuti, Siti Rani; Hasib, Abdullah; Aryaloka, Suhita; Moses, Ikechukwu Benjamin (Jurnal Medik Veteriner, 2024)
The problem most often encountered in fish farming is disease which can cause a decrease in fish production levels. Parasites cause one of the infectious diseases found in fish farming. The presence of parasites can cause a decrease in the quality of the growth of fish production. The purpose of this study was to identify the prevalence of ectoparasites on Nile tilapia in Sidoarjo, Indonesia. Ninety-six samples from two ponds were examined under the microscope to find out the presence of ectoparasite that exists in the outside body part of the fish. Samples were collected from skin, fins, tail, and gills using native methods and observed under a microscope in the Division of Parasitology Laboratory, Faculty of Veterinary Medicine, Universitas Airlangga. The results of this study showed 86 samples positively infected by ectoparasite and 10 showed negative. The ectoparasites found in this study were Trichodina sp., Chilodonella sp., Ichthyophthirius multifillis, Gyrodactylus sp., and Dactylogyrus sp. The highest prevalence is Trichodina sp. and Dactylogyrus sp. The number of fish infested by ectoparasite is 89.56%, this is classified in the usual category. The highest prevalence occurs in infestations of Trichodina sp. i.e.72.91% which were contained in the 70 samples. While the lowest prevalence was in Gyrodactylus sp. by 8.32% in 8 fish samples. Double infections from two different ponds were 70% within 33 samples which were included in the usual category.